2013
DOI: 10.5194/acp-13-1521-2013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regional changes in anthropogenic aerosols on rainfall of the East Asian Summer Monsoon

Abstract: The response of East Asian Summer Monsoon (EASM) precipitation to long term changes in regional anthropogenic aerosols (sulphate and black carbon) is explored in an atmospheric general circulation model, the atmospheric component of the UK High-Resolution Global Environment Model v1.2 (HiGAM). Separately, sulphur dioxide (SO<sub>2</sub>) and black carbon (BC) emissions in 1950 and 2000 over East Asia are used to drive model simulations, while emissions are kept constant at year 2000 level outside t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 43 publications
8
69
1
Order By: Relevance
“…This excessive equatorial Indian Ocean rainfall appears to be an inherent feature of the Met Office Unified model, with preferential model convection over areas with large amounts of available heat and moisture (Martin et al 2010). This bias is also found in other versions of the Met Office Hadley Centre Global Environmental Model (Levine and Turner 2012;Guo et al 2013). Despite these deficiencies, the simulated precipitation over East Asia compares fairly well with observations with an area averaged model precipitation of 2.99 mm day −1 over North China (35°N-45°N, 100°E-125°E) and 8.93 mm day −1 over South China (22.5°N-32.5°N, 100°E-120°E), in comparison with area averaged values of 2.70 and 6.58 mm day −1 in observations (Fig.…”
Section: Model Climate Over East Asiamentioning
confidence: 77%
See 4 more Smart Citations
“…This excessive equatorial Indian Ocean rainfall appears to be an inherent feature of the Met Office Unified model, with preferential model convection over areas with large amounts of available heat and moisture (Martin et al 2010). This bias is also found in other versions of the Met Office Hadley Centre Global Environmental Model (Levine and Turner 2012;Guo et al 2013). Despite these deficiencies, the simulated precipitation over East Asia compares fairly well with observations with an area averaged model precipitation of 2.99 mm day −1 over North China (35°N-45°N, 100°E-125°E) and 8.93 mm day −1 over South China (22.5°N-32.5°N, 100°E-120°E), in comparison with area averaged values of 2.70 and 6.58 mm day −1 in observations (Fig.…”
Section: Model Climate Over East Asiamentioning
confidence: 77%
“…In this study, we investigate the transient responses to an abrupt change in sulphur dioxide emissions from specific regions (Asia and Europe) in order to study physical processes of the EASM changes, using simulations with an atmospheric general circulation model. We chose to study the impacts of sulphur dioxide emissions since previous studies indicated that regional sulphate aerosols have a more important impact on the EASM than BC (e.g., Liu et al 2009;Guo et al 2013). A similar approach was used in Dong et al (2009) to investigate the transient adjustment of the atmosphere and land surface in response to an instantaneous doubling of CO 2 , and in Dong et al (2014) to investigate transient adjustment of the West African Monsoon to abrupt changes in regional sulphur dioxide emissions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations